Patriachal oppression of bedouin Egyptian women in selected novels by Miral al Tahawl: an analytical study in light of radical feminist theory - Hammood, Zainab Abd Ali (Tanjong Malim, 2020)
Patriachal oppression of bedouin Egyptian women in selected novels by Miral al Tahawl: an analytical study in light of radical feminist theory by Hammood, Zainab Abd Ali